Laboratory Investigations for Dewatering of Golden Horn Dredged Sludge with Geotextile Tubes - Berilgen, Saadet A.; Bulut, Begum Turan (TAYLOR & FRANCIS INC, 2016)
In this study, an effective means of dewatering the dredged material obtained from the sea-bottom in Istanbul is investigated through the use of additives and geotextile tubes (also known as geotubes, geotextile containers, and geotextile bags). Rapid dewatering test and geotube dewatering test are laboratory approaches, where the types and amounts of anionic and cationic additives for dewatering efficiency of dredged sludge can quickly and economically be examined. In this study, a best dosage amount of 1.5kg/tonne was used as flocculant solution preparation with distilled water. After this process, twelve homogeneous sludge-polymer admixtures were prepared by adding 0.1, 0.5, and 1.0% polymers (anionic and cationic) by weight of the dredged material in rapid dewatering tests and another twelve homogeneous sludge-polymer admixtures were prepared by adding 0.1, 0.25, and 0.50% polymers (anionic and cationic) by weight of the dredged material in geotube dewatering tests. The results indicated that Golden Horn dredged sludge could be successfully dewatered and retained by geotextile tubes. The use of chemical cationic polymers is recommended with Golden Horn dredged sludge rather than the anionic polymers. Results also showed that use of flocculants can significantly increase the retention capacity of geotubes.
Keywords: dredged sludge; polymers; dewatering; geotubes; CONSOLIDATION BEHAVIOR; FILTRATION PERFORMANCE; Engineering; Oceanography; Mining & Mineral Processing